PREPARATORY TRAINING FOR PRESCHOOL EDUCATION SPECIALIST IN THE CONTEXT OF THE EUROPEAN EXPERIENCE - Kuzina, Oksana (Educological discourse, 2019)
The article considers and analyzes the peculiarities of the professional training of educators in the developed countries of the world, and educators’ progressive achievements, and a high level of high school teacher training, which develop professional qualities in line with world standards, as the State standards of preschool education and all development programs. Children have stated an integrated approach to the educational process in the pedagogy. The works of leading scientists, which reveal various aspects of the future teachers training for pedagogical activities, are analyzed in the works of domestic scientists, in which the specificity of education, the state of pre-university vocational training, problems of higher education, various aspects of adult education, in particular integration of pedagogical training, foreign systems of pedagogical technologies of development, reform of European higher education in general. It is concluded that the systems of training teachers of preschool education in the leading European countries are different. They have their own peculiarities and their own promising experience, as well as the basic qualities of the training of future preschool specialists of European countries, not only is the system of organization of educational process in higher educational institutions established, but also the complex implementation of further training and professional development, the design of a new educational policy in the framework of the European integration processes that ensure the quality of preschool education in countries.